The Use of The Word Splash Strategy in Vocabulary Enhancement at Junior High School Level - Gabriela Elizabeth de Queljoe; Renata C. G. V. Nikijuluw; Smarty Jabez Samuel Satumalay (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2023)
This paper explores using the word splash strategy to enhance vocabulary at the Junior High School Level. Some researchers have applied the word splash strategy to help students learn vocabulary. The research showed that by using the word splash strategy, students could effectively motivate learning vocabulary. Students showed evidence of learning by using the word splash strategy. Word Splash is a learning strategy that stimulates thinking around a topic. The Word Splash Strategy allows students to learn new words and ideas before they start reading and helps them figure out how the word might relate. This strategy can help students improve their vocabulary by allowing them to predict words before they read the passage and connect new words or ideas to the passage's main idea.